Unlocking the potential of fondaparinux: guideline for optimal usage and clinical suggestions (2023) - Yin, Qinan; Han, Lizhu; Wang, Yin; Kang, Fengjiao; Cai, Fengqun; Wu, Liuyun; Zheng, Xingyue; Li, Lian; Dong, Li e; Dong, Limei; Liang, Shuhong; Chen, Min; et al. (Frontiers in Pharmacology, 2024)
Background: Thromboembolic disease is associated with a high rate of disability or death and gravely jeopardizes people's health and places considerable financial pressure on society. The primary treatment for thromboembolic illness is anticoagulant medication. Fondaparinux, a parenteral anticoagulant medicine, is still used but is confusing due to its disparate domestic and international indications and lack of knowledge about its usage. Its off-label drug usage in therapeutic settings and irrational drug use are also common. Objective: The aim of this guideline is to enhance the judicious clinical application of fondaparinux by consolidating the findings of evidence-based research on the drug and offering superior clinical suggestions. Methods: Seventeen clinical questions were developed by 37 clinical pharmacy experts, and recommendations were formulated under the supervision of three methodologists. Through methodical literature searches and the use of recommendation, assessment, development and evaluation grading techniques, we gathered evidence. Results: This guideline culminated in 17 recommendations, including the use of fondaparinux for venous thromboembolism (VTE) prevention and treatment, perioperative surgical prophylaxis, specific diseases, special populations, bleeding and overdose management. For different types of VTE, we recommend first assessing thrombotic risk in hospitalized patients and then administering the drug according to the patient's body mass. Fondaparinux may be used for anticoagulation prophylaxis in patients hospitalized for oncological purposes, in patients with atrial fibrillation (AF) after resuscitation, in patients with cirrhosis combined with portal vein thrombosis (PVT), in patients with antiphospholipid syndrome (APS), and in patients with inflammatory bowel disease (IBD). For bleeding caused by fondaparinux, dialysis may partially remove the drug. Conclusion: Currently, there is a lack of a dedicated antidote for the management of fondaparinux. The clinical investigation of activated prothrombin complex concentrate (APCC) or recombinant activated factor VII as potential reversal agents is still pending. This critical gap necessitates heightened scrutiny and research emphasis, potentially constituting a novel avenue for future inquiries into fondaparinux sodium. A meticulous examination of adverse events and safety profiles associated with the utilization of fondaparinux sodium will contribute significantly to a more comprehensive understanding of its inherent risks and benefits within the clinical milieu.